Impact of a soy drink on climacteric symptoms: an open-label, crossover, randomized clinical trial. (2nd June 2016) - Tranche, Salvador; Brotons, Carlos; Pascual de la Pisa, Beatriz; Macías, Ramón; Hevia, Eduardo; Marzo-Castillejo, Mercè
Abstract: Objectives : The objective of this study is to evaluate the effects of a soy drink with a high concentration of isoflavones (ViveSoy®) on climacteric symptoms. Methods : An open-label, controlled, crossover clinical trial was conducted in 147 peri- and postmenopausal women. Eligible women were recruited from 13 Spanish health centers and randomly assigned to one of the two sequence groups (control or ViveSoy®, 500 mL per day, 15 g of protein and 50 mg of isoflavones). Each intervention phase lasted for 12 weeks with a 6-week washout period. Changes on the Menopause Rating Scale and quality of life questionnaires, as well as lipid profile, cardiovascular risk and carbohydrate and bone metabolism were assessed. Statistical analysis was performed using a mixed-effects model. Results : A sample of 147 female volunteers was recruited of which 90 were evaluable. In both sequence groups, adherence to the intervention was high. Regular consumption of ViveSoy® reduced climacteric symptoms by 20.4% ( p = 0.001) and symptoms in the urogenital domain by 21.3% ( p < 0.05). It also improved health-related quality life by 18.1%, as per the MRS questionnaire ( p <0.05). Conclusion : Regular consumption of ViveSoy® improves both the somatic and urogenital domain symptoms of menopause, as well as health-related quality of life in peri- and postmenopausal women.